Insights into Host Cell Modulation and Induction of New Cells by the Corn Smut Ustilago maydis - Redkar, Amey; Matei, Alexandra; Doehlemann, Gunther (Frontiers in Plant Science, 2017)
Many filamentous fungal pathogens induce drastic modulation of host cells causing abnormal infectious structures such as galls, or tumors that arise as a result of re-programming in the original developmental cell fate of a colonized host cell. Developmental consequences occur predominantly with biotrophic phytopathogens. This suggests that these host structures result as an outcome of efficient defense suppression and intimate fungal-host interaction to suit the pathogen’s needs for completion of its infection cycle. This mini-review mainly summarizes host cell re-programming that occurs in the Ustilago maydis – maize interaction, in which the pathogen deploys cell-type specific effector proteins with varying activities. The fungus senses the physiological status and identity of colonized host cells and re-directs the endogenous developmental program of its host. The disturbance of host cell physiology and cell fate leads to novel cell shapes, increased cell size, and/or the number of host cells. We particularly highlight the strategies of U. maydis to induce physiologically varied host organs to form the characteristic tumors in both vegetative and floral parts of maize.